2016
DOI: 10.1177/0269215516646166
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and pain acceptance as mediators of the relationship between pain and performance of valued life activities in women and men with rheumatoid arthritis

Abstract: These findings highlight the importance of considering personal factors, such as pain acceptance and self-efficacy, in facilitating participation in valued life activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
(87 reference statements)
1
23
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to uncover the role of chronic pain acceptance in AS. The mean CPAQ score acquired from all the 167 participants was 62.4 (SD = 24.7), which was lower than that of patients with rheumatoid arthritis, as reported by Ahlstrand et al (24). Thus, these findings suggest that there exist complex interactions between different diseases and patients' psychological properties.…”
Section: Discussioncontrasting
confidence: 48%
“…To the best of our knowledge, this is the first study to uncover the role of chronic pain acceptance in AS. The mean CPAQ score acquired from all the 167 participants was 62.4 (SD = 24.7), which was lower than that of patients with rheumatoid arthritis, as reported by Ahlstrand et al (24). Thus, these findings suggest that there exist complex interactions between different diseases and patients' psychological properties.…”
Section: Discussioncontrasting
confidence: 48%
“…Preliminary research has also found that trait optimism is associated with lower levels of pain intensity and disability in individuals with chronic pain [ 30 ]. Previous observational studies have shown that pain self-efficacy partially mediates the longitudinal association between changes in pain and changes in disability in individuals with chronic low back pain [ 37 ], as well as pain self-efficacy and pain acceptance cross-sectionally mediate the association between pain intensity and engagement in valued activities in people with rheumatoid arthritis [ 35 ]. Several studies have found that self-efficacy beliefs [ 38 ] and pain acceptance [ 39 , 40 , 41 , 42 ] mediate the improvement in psychological and multidisciplinary pain treatments in individuals with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers evaluated the potential cross-sectional mediator role that positive psychological factors play in the association between musculoskeletal pain intensity and a variety of pain-related outcomes [ 34 , 35 ]. For example, pain self-efficacy was shown to cross-sectionally mediate the association between pain intensity and depression in a sample of individuals with fibromyalgia [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations